KEEFEKTIVAN INTEGRASI SINTAKS INKUIRI TERBIMBING DAN STAD (INSTAD) UNTUK MEMPERKECIL KESENJANGAN KETERAMPILAN METAKOGNISI SISWA AKADEMIK ATAS DAN BAWAH - Baskoro Adi Prayitno; Bowo Sugiharto (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2015)
This study aimed at investigating the influence of INSTAD model compared to guided inquiry, STAD and conventional toward metacognition skill, the influence of academic achievementtoward metacognition skill, and interaction of learning model and academic achievement toward metacognition skill. The method used in this study is a quasi-experimental research method with factorial design of 2x4. The population of this study is seventh grade students of all State Junior High School in Surakarta. The writers used random sampling technique with school criteria of high and low quality. The research findings showed that there is an influence on learning model of metacognition skill. INSTAD model and guided inquiry are not significantly different, but those are significantly different from the Conventional and STAD models toward metacognition skill. There is an influence on theacademic achievement toward metacognition skill. Upper academic students have higher metacognition skill than lower academic students do. There is interaction of learningmodel and academic achievement toward metacognition skill.